2012
DOI: 10.1051/0004-6361/201118744
|View full text |Cite
|
Sign up to set email alerts
|

A primordial star in the heart of the Lion

Abstract: Context. The discovery and chemical analysis of extremely metal-poor stars permit a better understanding of the star formation of the first generation of stars and of the Universe emerging from the Big Bang. Aims. We report the study of a primordial star situated in the centre of the constellation Leo (SDSS J102915+172927). Methods. The star, selected from the low-resolution spectrum of the Sloan Digital Sky Survey, was observed at intermediate (with X-Shooter at VLT) and at high spectral resolution (with UVES… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
132
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(147 citation statements)
references
References 78 publications
12
132
3
Order By: Relevance
“…Since it is not visible, we are able to place an upper limit [C/Fe]< +0.7. However, our derived metallicity is higher than that determined by Caffau et al (2012), due to the ISM contribution to the Ca ii H and K lines. The metallicity is compatible with our analysis in Aguado et al (2017) with ISIS and UVESsmoothed data.…”
Section: Testing the Methodology With J1019+1729contrasting
confidence: 90%
“…Since it is not visible, we are able to place an upper limit [C/Fe]< +0.7. However, our derived metallicity is higher than that determined by Caffau et al (2012), due to the ISM contribution to the Ca ii H and K lines. The metallicity is compatible with our analysis in Aguado et al (2017) with ISIS and UVESsmoothed data.…”
Section: Testing the Methodology With J1019+1729contrasting
confidence: 90%
“…Our analysis of the SDSS spectrum of this relatively bright star for our sample (g = 17.3) yields estimates of T eff = 5888 K, log g = 4.47, and [Fe/H] = −4.4, which compare well with those from the high-resolution analysis by Caffau et al (2012), namely T eff = 5811 ± 150 K, log g = 4.0 ± 0.5, and [Fe/H] = −4.89 ± 0.10.…”
Section: Additional Validationssupporting
confidence: 77%
“…In addition, the latest findings by Caffau et al (2011Caffau et al ( , 2012) push the lowest metallicity at which low mass stars can form, increasing the need of detailed models for this class of stars. All these results reinforce the necessity of detailed studies of the PIE, both with hydrodynamic simulations and stellar evolutionary models to achieve a more realistic picture of the its properties.…”
Section: Discussionmentioning
confidence: 99%
“…III stars can be formed in multiple systems with a flat protostellar mass function (M ∼ 0.1−10 M ). Moreover, the recent discovery of an EMP star with a metallicity of [Fe/H] = −4.89 and no enhancement in CNO elements (Caffau et al 2011(Caffau et al , 2012, which results in the lowest total metallicity Z ≤ 10 −4 Z observed in a star, also puts into question the claims of a minimum metallicity required for the formation of low-mass stars (Bromm & Loeb 2003;Schneider et al 2003). These results reinforce the necessity of determining the mass range of the stars responsible for the chemical signatures that are observed in EMP stars to constrain the initial mass function in the early Universe.…”
Section: Introductionmentioning
confidence: 99%